Fabrication of the liquid crystalline periodic waveguiding structures by means of the photo-polymerization process - Turowski, Bartłomiej; Rutkowska, Katarzyna Agnieszka (Photonics Letters of Poland, 2017)
Photonic structures in a form of the waveguide channels, with periodic spatial changes in refractive index in the wavelength scale, are typically manufactured based on well-developed silica and gallium arsenide technology [1], as well as with use of the high-precision lithography. The main disadvantage related to practical application of such devices is that their optical properties cannot be altered after fabrication. Due to this fact, liquid crystalline periodic waveguiding structures, manufactured with use of the photo-polymerization process, have been proposed in this work. Importantly, propagational characteristic of such photonic structures can be easily adjusted during fabrication procedure, and then may be also dynamically tuned by e.g. applied external voltage, as presented in this communication. Full Text: PDF References M.J. Ablowitz, Z.H. Musslimani, "Discrete spatial solitons in a diffraction-managed nonlinear waveguide array: a unified approach", Physica D: Nonlinear Phenomena 184(1), 276 (2003). CrossRef L. Vicari, Optical applications of liquid crystals, CRC press, 2016. CrossRef J. Yan, S.-T. Wu, "Effect of Polymer Concentration and Composition on Blue Phase Liquid Crystals", J. Display Technol. 7, 9 (2011). CrossRef J. Schirmer et al., "Birefringence and Refractive Indices Dispersion of Different Liquid Crystalline Structures", Mol. Cryst. Liquid Cryst. 307, 17 (1997). CrossRef D. Xu et al., "Blue phase liquid crystals stabilized by linear photo-polymerization", Appl. Phys. Lett. 105, 8 (2014). CrossRef I. Dierking et al., "Stabilising liquid crystalline Blue Phases", Soft Matter 8, 4355 (2012). CrossRef K. Kang, L.C. Chien, S. Sprunt, "Polymer-stabilized cholesteric liquid crystal microgratings: a comparison of polymer network formation and electro-optic properties for mesogenic and non-mesogenic monomers", Liquid Crystals 29, 9 (2002). CrossRef K.A. Rutkowska, M. Chychłowski, U.A. Laudyn, "Polymer-stabilized periodic waveguiding structures in liquid crystalline materials", Proc. SPIE 10325 (2017). CrossRef